Trichohyalin gene expression is negatively correlated with the severity of dermatitis in a canine atopic dermatitis model - Marsella, Rosanna; Ahrens, Kim; Wilkes, Rachel; Munguia, Nathalie (Frontiers in Veterinary Science, 2024)
Introduction Canine atopic dermatitis (AD) closely mimics human AD and is recognized as a beneficial animal model. House dust mites (HDM) are a common allergen for both species. The effects of chronic exposure to HDM on the skin have not been studied in this animal model, and it is not known how changes in gene expression correlate to the severity of dermatitis. Methods We used an established canine model of AD and took biopsies before HDM exposure (D0) and five times during repeated allergen challenges (on Days 1, 2, 8, 15, and 29, hereafter referred to as D1, D2, D8, D15, and D29). The severity of dermatitis was scored on the same days. Results Trichohyalin (TCHH) gene expression decreased the most (15-fold decrease on D29 vs. D0) and negatively correlated with the severity of dermatitis. Gap-junction protein gene expression increased over 3-fold on D1, D8, and D29 and positively correlated with the severity of dermatitis. Compared to D0, IL-31 gene expression significantly increased on D8 (p = 0.0098), D15 (p = 0.0068), and D29 (p = 0.0187), but the correlation with the severity of dermatitis did not reach significance. Discussion This is the first report on trichohyalin, a protein belonging to the S100 family, and gap-junction protein gene expression in the context of the clinical severity of AD. We propose that these proteins should be further investigated to better understand their role in this complex disease.